MEASURING SATISFACTION USER WEBSITE WWW.QOO10.CO.ID USING DELONE AND MCLEAN MODELS - Yuningsih, Yuyun; Puspita, Ari; Dahlia, Dahlia (Kresnamedia Publisher, 2020)
The research to measure customer satisfaction with the use of a product or service sold on online shopping sites that can meet their needs as expected. The research method used in this study is a survey method, the authors distribute questionnaires to men or women aged 17-40 years who have already or frequently shop online through the website www.qoo10.co.id. This research uses Delone and McLean models and is assisted with AMOS (Analysis of Moment Structure) software. Delone and McLean models can facilitate researchers in determining the variables that affect measuring website user satisfaction. the results of this study are in the form of a chart that concludes that the quality of the information system influences user satisfaction. The quality of the system affects the user, user satisfaction affects the user, and usage influences the benefits of the web www.Qoo10.co.id with the value of Chi-Square 7.015 and a Probability value of 0.83.